Análise das comparações e correlações entre problemas de comportamento, práticas parentais e habilidades sociais - Rovaris, Jéssica Aline [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Considering the relevance of evaluating educational practices as well as their relationship with infant behaviors, this paper aimed to describe, compare and correlate maternal educational practices the behavior of children classified by problems of behaviors, education and gender. This research involved 155 mothers of children enrolled in públic schools. These children were in Kindergarten and elementary schools, they had both genders (boys and girls). The following instruments were answered: CBCL, RE-HSE-P e QRSH-P (version for parents). Were conducted Chi-square tests and Student's t-test to comparison analysis, Pearson correlations test and linear regression. Results demonstrated that, for kindergarten and elementary school children, the repertory of social skills constitutes protective factor and the negative practices constitute risk factor for behavioral problems. The girls, especially in elementary school grades, were identified as more skilled and more frequently exposed to positive maternal practices. On the other hand, boys in kindergarten period received the biggest number of behavioral problems and exposure to negative educational maternal practices, indicating the importance of considering the child's gender in the evaluation of the behaviors emitted in the mother-children relationship. This study also found that mothers of children with and without diagnosis of behavioral problems present social skills in the interaction with their children. What seems to distinghish each group is the frequency of the application of negatives and positive practices. Kindergarten children's mothers exhibit skilled even facing their children's behavioral problems, unlike the behaviors emitted in the interaction with elementary school children, in which the usage of negative practices was more frequent. Other important aspect is the confirmation that mothers of clinical group children exhibit more difficulties to identify and reinforce...

Diante da relevância em se avaliar as práticas educativas, bem como sua relação com os compartamentos infantis, neste trabalho, buscou-se descrever, comparar e correlacionar práticas educativas maternas com comportamentos de crianças diferenciadas por problema de comportamento, escolaridade e sexo. Participaram do estudo 155 mães de crianças matriculadas na rede pública de ensino, que cursavam a pré escola ou ensino fundamental, de ambos os sexos. Foram respondidos aos instrumentos: CBCL, RE-HSE-P e OQSH-P (versão para país). Foram conduzidos os testes Qui-quadrado e t de Student para análises de comparação, o teste de correlação de Pearson e a regressão linear. Os resultados demonstraram que, para crianças em idade pré-escolar e escolar, o repertório de habilidades sociais se constitui fator de proteção e as práticas negativas fator de risco para problemas de comportamento infantil. As meninas, especialmente das séries do ensino fundamental, foram identificadas como as mais habilidosas e expostas, mais frequentemente, às práticas maternas positivas. Ao contrário, dosmeninos pré-escolares, para quem foi atribuído maior número de problemas de comportamento e exposição às práticas educativas maternas negativas, sinalizando a importância de se considerar o sexo da criança na avaliação dos comportamentos emitidos na relação-mães-filhos. Constatou-se, também, que mães de crianças com e sem diagnóstico de problemas de comportamento apresentam habilidades sociais de interação com os filhos, o que parece diferenciar cada grupo é a frequencia com que práticas negativas se positivas são utilizadas. As mães de pré-escolares apresentaram comportamentos habilidosos mesmo diante dos problemas de comportamentos dos filhos, diferente dos comportamentos emitidas nas interações com as crianças em idade escolar, em que o uso das práticas negativas foi mais frequente. Outro aspecto importante é a...
Keywords: Psicologia infantil; Educação; Pratica de ensino; Habilidades sociais; Child psychology